A new species of the genus Petersenidia Lelej (Hymenoptera: Mutillidae) from Indonesia, eastward of Wallace’s line - Lelej, Arkady S. (Zootaxa, 2021)
Petersenidia mikhailovi sp. nov. (♀, Indonesia: Sulawesi) is described and illustrated. The new species is related to P. macassarica (Zavattati, 1914) by having a median longitudinal carina on the basal half of metasomal tergum 2, but differs by the carina being shorter and lower, by the lack of a posterior interrupted pale fringe on metasomal tergum 2 and by a smooth pygidium. The lectotype of Mutilla macassarica Zavattari, 1914 is designated.